Turkey's Foreign Trade and New Markets for Turkey - (:unkn) unknown (IGI GLOBAL, 2016)
The share of developing countries in the world trade is increasing every day. According to an assessment made by the World Trade Organization (WTO), a share of developing countries in the world export is expected to rise by 8.5% in the years ahead. Turkey's share in the world trade is around 1%, and it is expected to increase up to 1.5% by 2023. Turkey is ranked 22nd in the world export and 15th in the world import of goods. Turkey's current problems are account and trade deficits. New markets will potentially offer an opportunity to overcome both account and trade deficits. The aim of this chapter is to define new export markets for Turkey. According to the survey results, Turkey may potentially increase its export to the USA. Apart from the USA, Germany and Russia will continue to serve as export markets for Turkey in the years ahead. Therefore, Turkish companies will maintain their existing trade relations with these countries.